Ibragim Gafurov Is A Storyteller - Sultonova, Vazira (FILOLOGIYA UFQLARI JURNALI, 2024)
This article analyzes the skill of creating a historical story by Ibrahim Gafurov, a skilled translator, journalist and writer. Such stories as “Gala”, “Mother Dargahida (Alif)”, “Murid”, “The Boy Playing in the Slaughterhouse”, “Yellow Flowers of Bobarahim” about Boborahim Mashrab, which form a cycle of stories in the writer’s work, were studied. The story “The Boy Playing in the Slaughterhouse” is highlighted as a separate object and the writer’s writing skills are emphasized in it. The title of the work, plot, volume of artistic expression, visual means, and elements of artistic language were taken into account. The role and function of each in the work is analyzed depending on the skill of the writer.